SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON TENAGA KERJA DI KOTA PONTIANAK DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Lisnawanty, Lisnawanty; Dina, Fara; Sihombing, Daniel Oktodeli (LPPM Universitas Nusa Mandiri, 2018)
Labor is an important part that supports operations within a company. Manpower requirements planning is part of the recruitment program preparation activities to do selection so as to obtain workers who meet the qualifications in a company. However, not all selection processes succeed by getting candidates for work that are in line with company qualifications. Therefore, this study discusses the Decision Support System for the Selection of Prospective Workers in Pontianak City (SIPEKERJA) which is web-based. The method used in this study is the Simple Additive Weighting (SAW) method. Variables that become the main criteria in the Decision Support System for Selection of Prospective Laborers include gender, age, education level, field of expertise, and work experience. The system that has 3 levels of access (they are admin, prospective workers, and companies) is expected to be able to support the company in determining prospective workers according to the criteria expected by the company to occupy a certain part of the company.